Analysis of Experiments of a New Approach for Test Quality Evaluation - Haroutunian, Mariam E.; Avetisyan, Varazdat K. (Mathematical Problems of Computer Science, 2021)
In the previous paper [1] we suggested a new model of test quality evaluation based on Information measures such as Shannon entropy and average mutual information. To establish the practical bounds of these measures and the required number of examinees, some experiments were conducted. In this paper the analysis of these experiments are provided.